2024
DOI: 10.1002/chem.202304318
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Immune System TIM‐3 Protein with a Model Cellular Membrane Containing Phosphatidyl‐Serine Lipids

Anastasiia Delova,
Andreea Pasc,
Antonio Monari

Abstract: T cell transmembrane, Immunoglobulin, and Mucin (TIM) are important immune system proteins which are especially present in T‐cells and regulated the immune system by sensing cell engulfment and apoptotic processes. Their role is exerted by the capacity to detect the presence of phosphatidyl‐serine lipid polar head in the outer leaflet of cellular membranes (correlated with apoptosis). In this contribution by using equilibrium and enhanced sampling molecular dynamics simulation we unravel the molecular bases an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 69 publications
0
0
0
Order By: Relevance
“…49 Recently, by using enhanced sampling and extended Molecular Dynamics (MD) simulations the thermodynamic parameters of the interaction between the IvG domain and PDS containing lipids have also been determined. 16 Notably, we have shown that the inclusion of the lipid in the binding pocket is barrierless and favored by a free energy driving force of about 15-20 kcal/mol. 16 While the polar head is held tight between the FG and CC' loops, the lipid tails remain globally parallel to the membrane axis and stretch away from the IvG surface.…”
Section: Toc Graphic Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…49 Recently, by using enhanced sampling and extended Molecular Dynamics (MD) simulations the thermodynamic parameters of the interaction between the IvG domain and PDS containing lipids have also been determined. 16 Notably, we have shown that the inclusion of the lipid in the binding pocket is barrierless and favored by a free energy driving force of about 15-20 kcal/mol. 16 While the polar head is held tight between the FG and CC' loops, the lipid tails remain globally parallel to the membrane axis and stretch away from the IvG surface.…”
Section: Toc Graphic Introductionmentioning
confidence: 83%
“…16 Notably, we have shown that the inclusion of the lipid in the binding pocket is barrierless and favored by a free energy driving force of about 15-20 kcal/mol. 16 While the polar head is held tight between the FG and CC' loops, the lipid tails remain globally parallel to the membrane axis and stretch away from the IvG surface.…”
Section: Toc Graphic Introductionmentioning
confidence: 83%
See 3 more Smart Citations